Barriers in Running Construction SME – Case Study on Introduction of Agile Methodology to Electrical Subcontractor. (2015) - Nowotarski, Piotr; Paslawski, Jerzy
Abstract: The article presents agile management approach to manage the construction process, which is based on management of IT projects and ideas to improve quality. Initially focused on the application during the implementation of IT project, works were aimed to adjust to changing customer requirements. The main idea of agile in the presented approach to adapt to the changes instead of strict implementation of the plan. The idea of introducing agile management in the construction industry, exemplified with SME company electrical subcontractor, for which the most important problems and barriers of doing business were discussed, is presented in the paper. On the basis of the research, authors proposed solutions and methods in accordance with the agile idea.